Childhood malnutrition is associated with maternal care during pregnancy and childbirth: a cross-sectional study in Bauchi and Cross River States, Nigeria - Candyce Hamel; Joseph Enne; Khalid Omer; Ndem Ayara; Yahaya Yarima; Anne Cockcroft; Neil Andersson (SAGE Publishing, 2015)
Background. Malnutrition remains an important cause of childhood morbidity and mortality; the levels of childhood malnutrition in Nigeria are among the highest in the world. The literature supports many direct and indirect causes of malnutrition, but few studies have examined the link between maternal care during pregnancy and childbirth and childhood malnutrition. This study examines this potential link in Bauchi and Cross River states in Nigeria. Design and methods. In 2011, a household survey collected information about children under four years old and their mothers' last pregnancy. Trained fieldworkers measured mid-upper arm circumference (MUAC) of children aged 6-47 months. We examined associations with childhood malnutrition in bivariate and multivariate analysis. Results. Some 4.4% of 3643 children in Cross River, and 14.7% of 2706 in Bauchi were malnourished (MUAC z-score). In both states, a child whose mother had fewer than four government antenatal care visits was more likely to be malnourished (Cross River: OR 1.85, 95%CIca 1.33-2.55; Bauchi: OR 1.29, 95%CIca 1.02-1.63). In Bauchi, a child whose mother who rarely or never discussed pregnancy and childbirth with her husband (OR 1.34, 95%CIca 1.07-1.68), and who did not have her last delivery attended by a skilled health worker was more likely to be malnourished (OR 1.50, 95%CIca 1.09-2.07). Conclusions. These findings, if confirmed in other studies, suggest that poor care of women in pregnancy and childbirth could pose a longer term risk to the health of the child, as well as increasing immediate risks for both mother and child.